Palisaded granulomatous neutrophilic dermatosis in systemic lupus erythematosus - Prachi Srivastava; Anand Kumar Vaggu; K Sujatha; Jaideep Khare (Wolters Kluwer Medknow Publications, 2017)
Palisaded granulomatous neutrophilic dermatosis (PGND) is a cutaneous reaction pattern seen in association with some systemic diseases. It is mostly seen in adult patients with only three case reports of these lesions in children. We hereby report a 12-year-old female child with systemic lupus erythematosus flare having PGND, showing two different morphologies clinically which were also confirmed on histology depicting the much-speculated evolution of the disease. We are reporting the case for the rarity in pediatric patients, the presentation of different morphological variants in the same patient as well as the uncommon site of involvement.